2017
DOI: 10.1111/camh.12241
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating depression among orphaned and vulnerable adolescents: a randomized controlled trial of interpersonal psychotherapy for groups in South Africa

Abstract: Background: Children and adolescents affected by HIV are at elevated risk of depression, yet research on related interventions in this population is scarce in sub-Saharan Africa. This study sought to examine the effects of interpersonal psychotherapy for groups (IPTG) on depressive symptomology among orphaned and vulnerable adolescents in South Africa. Method: A cluster randomized controlled trial wherein adolescents ages 14-17 enrolled in community-based programming for HIV-affected and vulnerable families we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 53 publications
0
27
0
1
Order By: Relevance
“…Sixteen studies were carried out at sub-Saharan African research institutions [ 21 , 22 , 32 , 33 , 37 39 , 41 , 43 , 44 , 47 , 50 52 , 54 56 ] the majority in South Africa (n = 9). Nineteen of the studies were conducted in collaboration with researchers from HIC or other LMIC [ 13 , 22 30 , 35 , 36 , 40 , 43 , 48 , 49 , 53 , 55 , 57 ] and four studies were carried out by researchers based in HIC [ 34 , 42 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies were carried out at sub-Saharan African research institutions [ 21 , 22 , 32 , 33 , 37 39 , 41 , 43 , 44 , 47 , 50 52 , 54 56 ] the majority in South Africa (n = 9). Nineteen of the studies were conducted in collaboration with researchers from HIC or other LMIC [ 13 , 22 30 , 35 , 36 , 40 , 43 , 48 , 49 , 53 , 55 , 57 ] and four studies were carried out by researchers based in HIC [ 34 , 42 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies used a cross-sectional study design, four studies used baseline data from randomized control trials [ 35 , 36 , 38 , 53 ], and two were cohort studies [ 30 , 57 ]. The most common sampling method was stratified or cluster random sampling.…”
Section: Resultsmentioning
confidence: 99%
“…A challenge in the adaptation process was to decide on the number of sessions. Previous evaluations of group IPT for adolescents in LMICs have included 16 sessions [39,60]. A study of individual IPT for adolescents found that a reduction in depressive symptoms of 16% or more at week 4 predicted remission at week 16 [73].…”
Section: Discussionmentioning
confidence: 99%
“…Our experience from practice groups suggested that adolescents took around four sessions to feel comfortable and contribute to group discussions, and that the eight group sessions outlined in the WHO Manual would be insufficient. Interventions involving 16 group sessions have been tested in other LMICs [39,60], however the remote location of our study was a potential barrier to attendance and we anticipated high drop-out rates with 16 sessions. As a compromise we therefore increased the number of group sessions to 12 (Fig.…”
Section: Methodshow Treatment Goals Are Achievedmentioning
confidence: 99%
“…A randomized trial of a structured family-centered mental health promotion and HIV prevention program in Kenya found reduced sexual risk behavior among adolescents at one month post-intervention (Puffer et al, 2016). However, in spite of the interventions' mental health focus, psychological improvements were not found among participants in either study (Puffer et al, 2016;Thurman, Nice, Taylor, & Luckett, 2017). Let's Talk shows potential to reduce psychological distress among adolescents and their caregivers while also bolstering other protective individual and family-level factors, which could plausibly support HIV preventive behavior (DiClemente et al, 2008).…”
Section: Discussionmentioning
confidence: 99%